Thermal evaluation of a hermetic transcutaneous energy transfer system to power mechanical circulatory support devices in destination therapy. Issue 9 (8th April 2020) - Au, Shun Long Cyril; McCormick, Daniel; Lever, Nigel; Budgett, David
Abstract: Current generation left ventricular assist devices (LVADs) are powered by a percutaneous driveline. The high prevalence of driveline infections has motivated the development of transcutaneous energy transfer (TET) systems which eliminate driveline associated complications by wirelessly delivering power across the skin. Destination therapy (DT) requires long‐term reliable operation of the TET electronics suggesting the use of hermetic packaging techniques as used in all other chronically implanted devices. TET coils dissipate heat during operation and in order for the technology to be suitable for patient use, sufficient power must be delivered while maintaining temperatures at levels deemed safe. The heating of a TET system designed for DT which uses hermetic packaging technology was evaluated in silico and in vivo. A numerical model was used to evaluate the temperature of the TET coils. The TET system was fabricated and assessed in vivo using an ovine model. The receiving coil was implanted subcutaneously in a sheep and the transmission coil placed in contact with the skin and concentric to the implanted coil. Temperatures of the system were measured using sensors fixed to the surface of the coils. Numerical modeling indicated that the maximum temperatures of the primary and secondary coil surfaces were 38.13°C and 38.41°C, respectively, when delivering 10 W continuously. Stable temperatures were observed in vivo after 70 minutes and the maximum skin and implant surface temperatures were 37.73°C and 38.31°C, respectively. This study showed that a hermetic, chronically implantable TET system is thermally safe when continuously delivering 10 W of power, sufficient to power modern LVADs.